FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN SELFDIRECTED LEARNING PADA MAHASISWA KEPERAWATAN - Andri Purwandari (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
ABSTRACTBackground: The PBL method requires students to emphasize more independent learning in  order to identify goals and plan strategies to meet their needs. There are many factors that can  affect the ability of SDL students, so assistance from educators is needed and literature support to support the SDL process is better. Objective: To ﬁ nd out the factors that inﬂ uence SDL’s ability in ﬁ rst, second, third, and fourth year nursing students.Methods : The study used descriptive qualitative methods by conducting FGDs and in-depth interviews. Results : The indepth interview results found a theme that included learning preparation and factors that inﬂ uenced SDL.Conclusion: There are factors that inﬂ uence SDL, including: inhibiting factors: mood and motivation, campus facilities, boredom, interpersonal skills, adaptation, and time management; inhibiting factor: parental support.